How does completing an Ironman triathlon affect postural control? - Hugo Eduardo de Amorim; Gilmar Moraes Santos; Luis Mochizuki; Evangelos Pappas; Vanessa Lima Silva; Patrícia Parizotto; Carolina Buzzi da Silveira (Universidade Federal de Santa Catarina, 2020)
Despite the increase in the number of Ironman competitions worldwide, thousands of athletes have been joining Ironman experience but only a few studies have been published on the effects of this competition on postural control. This study aims to investigate the ability to maintain a static posture in three different positions before and after an Ironman competition and the blood glucose level behavior. Forty-nine volunteers underwent balance evaluation using the force plate VSRTM Sport. The area of the center of gravity (ACOG) was assessed pre- and post-competition in the bipodal, unipodal, and tandem postures. Glucose levels were also assessed concurrently. The ACOG findings showed a significant post-competition increase in the three postures assessed, with no significant interaction between the postures. The glucose test showed an increase in the post-competition glycemic levels. The findings showed reduced postural control, suggesting that prolonged exercise stimulation could lead to a disturbance in postural control.